Ecological analysis of the fish trematode fauna of the Lower Kura - Y.V. Shakaraliyeva (Вісник Харківського Національного Університету Імені В.Н. Каразіна: Серія Біологія)
In 2007-2022, in three sections of the lower reaches of the Kura River, 933 cyclostomes and fish belonging to 38 species were subjected to complete parasitological dissections, and 40 species of trematodes were discovered. Of these, 25 species complete their development in fish, and 15 species in fish-eating birds. 24 species parasitize in the fish intestines, 5 species in the lenses of fish eyes, and 1-2 species of trematodes are localized in other organs. Most of the discovered species of trematodes are freshwater forms; typically marine are only 4 species, which were found in marine fish that come here from the Caspian Sea. The examined fish belong to five trophic groups: ichthyophages, benthophages, planktophages, phytophages and detritiphages. In the ichthyophages were dominated by trematodes, which complete their development in fish. Apparently, these parasites enter the body of ichthyophages for the most part by eating fish infected by them. In the remaining trophic groups, the fauna of trematodes was significantly dominated by species parasitizing fish at the metacercaria stage. In the lower section of the Lower Kura, 37 species were found, of which 12 complete their development in fish-eating birds. This comparative richness of trematode fauna of lower section is due to the fact that it contains many more species of fish than other sites; the current speed is much lower and this promotes the development of mollusks - the first intermediate hosts of trematodes; there are a large number of fish-eating birds - the definitive hosts of many species of fish trematodes; the current carries here infected intermediate hosts and trematode cercariae from more upper sections; only here marine fish species were examined and marine trematodes were discovered; only here the lamprey was studied and one of its characteristic trematodes was faund. In the fish of the middle section, 26 species of trematodes were noted, of which 13 species complete development in fish-eating birds. Here the fauna of fish trematodes is somewhat poorer than in the lower section, but here there are more species of trematodes whose cercariae actively penetrate fish. This is due to the fact that not far from the point of collecting the material, Lake Sarysu is located, where a large number of fish-eating birds live. In fish living in the upper section, 22 species of trematodes were found, of which 10 species complete their development in fish-eating birds. Among all the noted trematodes, 7 species are pathogens of fish diseases and 1 species is dangerous to human.